Tweedracht maakt macht. De PvdA, de doorbraak en de ontluikende polarisatiestrategie (1946-1966) - Mellink, B. (BMGN - Low Countries Historical Review, 2011)
Divide and Rule: The Dutch Labour Party (PvdA), the Breakthrough and the Emerging Polarisation Strategy (1946-1966) In 1966, after a lengthy debate in the Dutch parliament, the Cals cabinet came to a sudden end. As a motion proposed by Norbert Schmelzer, the parliamentary leader of the prime minister’s own Catholic party precipitated the cabinet’s fall, ‘Schmelzer’s Night’ received an iconic status in Dutch political history. Many historians have interpreted Schmelzer’s Night as the birth of a Social Democratic ‘polarisation strategy’: differences between Left and Right were exaggerated in order to divide the confessional parties along ideological lines. Established analyses ascribe the development of this polarisation strategy to the ascendancy of a younger generation in Dutch politics. This article argues instead that the polarisation strategy of the late 1960s was not so much caused by a new generation, but rather emerged as a consequence of postwar Social Democrats’ efforts to abolish pillarisation (verzuiling) in Dutch society.